MODEL PENDIDIKAN PEREDAM PEMIKIRAN DAN GERAKAN RADIKAL BELAJAR DARI KUDUS - Moh Rosyid (Pascasarjana IAIN Kudus, 2017)
Educational institutions that produce educated generation is a place of reliance on the growth of generations berakhlakul karimah, friendly, courteous, and obey the rules of the country and religion. However, in reality, there is an educated generation but a terrorist actor. This happens because his life is in the environment (non-educational institutions) are coloring his mindset. Thus, the social environment contributes to the creation of a radical or polite generation. The consequence that must be done by formal and non formal education institutions is to change the learning patterns that text book into education that comes to the field with the content of the values of internal tolerance and inter-religious people. It is also necessary to realize the education of Bela Negara which is being worked by the Ministry of Defense RI era Jokowi-JK President. Tolerant education and state defenses are part of the effort to counter radical reasoning so that educators need to produce learning tips that do not dwell on class and text, it is also necessary to create an education that puts forward the real facts of social as a matter of study. The occurrence of radical reasoning because life is like a frog in a shell so that something different is identified with error. The need for intergovernmental and social elements to raise awareness that true education is the implementation of education in the home environment, community environment, and in educational institutions as a whole, not only in formal educational institutions only. Consequently, the need for learning innovation together in realizing an educated generation with smart and moral potential. Educational tips need to promote tolerant education in order to become a fanatic generation in dealing with differences in ethnicity, religion, and social strata in their environment. This effort is reinforced by the fact that terrorist networks have become an epidemic of acute illness in this country. In fact, the majority of educated perpetrators of terror, both formal education and non-formal religious education (Islamic).